Association studies of cytochrome P450, family 2, subfamily E, polypeptide 1 (CYP2E1) gene polymorphisms with acute rejection in kidney transplantation recipients. (8th May 2014) - Kim, Su Kang; Park, Hae Jeong; Seok, Hosik; Jeon, Hye Sook; Lee, Tae Won; Lee, Sang Ho; Moon, Ju Young; Ihm, Chun Gyoo; Kim, Tae Hee; Kim, Yeong Hoon; Kang, Sun Woo; Park, Seok Ju; et al.
Abstract Recent studies have shown that single‐nucleotide polymorphisms (SNPs) are associated with allograft rejection in kidney transplantation recipients. We evaluated the possible association between SNPs of the cytochrome P450, family 2, subfamily E, polypeptide 1 (CYP2E1) gene, and acute rejection (AR) among renal transplant patients in a Korean population. We conducted a case–control association study in 63 AR and 284 non‐AR kidney transplant recipients. The SNPs of CYP2E1 were genotyped by direct sequencing. Recipient sex (p = 0.023) and the use of tacrolimus (p = 0.017) were significantly different between the two groups. The use of mycophenolate mofetil (MMF) and antibody induction therapy was significantly lower in the AR group. Multiple logistic regression models (codominant, dominant, recessive, and log‐additive models) adjusted by sex and type of immunosuppressive regimens were applied to determine the odds ratios (ORs), 95% confidence intervals (CIs), and p‐values. The rs2515641 of CYP2E1 showed significant differences between the AR patient group and non‐AR group (p = 0.003, OR = 2.55, 95% CI = 1.37–4.75 in the codominant 1 model; p = 0.002, OR = 2.61, 95% CI = 1.43–4.77 in the dominant model; p = 0.0035, OR = 2.13, 95% CI = 1.29–3.50 in the log‐additive model). The allele of the rs2515641 SNP also showed a significant association (p = 0.004, OR = 1.99, 95% CI = 1.24–3.21). This study suggests that the CYP2E1 polymorphism may be related to the development of AR in Korean kidney transplantation recipients.